2021
DOI: 10.1164/rccm.202012-4447le
|View full text |Cite
|
Sign up to set email alerts
|

Lung Recruitability Evaluated by Recruitment-to-Inflation Ratio and Lung Ultrasound in COVID-19 Acute Respiratory Distress Syndrome

Abstract: A substantial proportion of patients with coronavirus disease 2019 (COVID-19) admitted to intensive care units (ICU) requires invasive mechanical ventilation for acute respiratory distress syndrome (ARDS), which is still associated with a high mortality rate (1). Applying the optimal positive end-expiratory pressure (PEEP) to ensure lung recruitment while limiting lung hyperinflation, remains challenging in ARDS (2, 3). Yet, there are few simple tools that might help personalize the level of PEEP in those pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 10 publications
1
19
1
Order By: Relevance
“…The response to prone position, in terms of oxygenation and respiratory mechanics, would differ according to the potential for lung recruitment in supine position in COVID-19-ARDS [ 3 ]. Recruitment-to-inflation ratio (R/I), which is measurable with almost all modern respirators, allows, at bedside, the distinction between patients with a low or high potential for lung recruitment [ 4 ], including in those with COVID-19-ARDS [ 5 ]. This tool may henceforth help clinicians to set adequate positive end-expiratory pressure (PEEP) levels in ARDS [ 4 ].…”
mentioning
confidence: 99%
“…The response to prone position, in terms of oxygenation and respiratory mechanics, would differ according to the potential for lung recruitment in supine position in COVID-19-ARDS [ 3 ]. Recruitment-to-inflation ratio (R/I), which is measurable with almost all modern respirators, allows, at bedside, the distinction between patients with a low or high potential for lung recruitment [ 4 ], including in those with COVID-19-ARDS [ 5 ]. This tool may henceforth help clinicians to set adequate positive end-expiratory pressure (PEEP) levels in ARDS [ 4 ].…”
mentioning
confidence: 99%
“…Stevic et al simultaneously assessed lung recruitability using both recruitment-to-inflation (R/I) ratio and lung ultrasound aeration score in a prospective observational study of 24 patients with novel coronavirus disease-associated ARDS. 132 The R/I ratio was calculated by the compliance of recruited lung divided by the lung compliance at low PEEP, 133 while the lung ultrasound aeration score was determined according to the method described by Bouhemad et al 129 Investigators found that an R/I ratio of 0.7 correlated with lung ultrasound aeration score, further validating the use of ultrasound-guided lung recruitment. 132 …”
Section: Methodsmentioning
confidence: 99%
“… 132 The R/I ratio was calculated by the compliance of recruited lung divided by the lung compliance at low PEEP, 133 while the lung ultrasound aeration score was determined according to the method described by Bouhemad et al 129 Investigators found that an R/I ratio of 0.7 correlated with lung ultrasound aeration score, further validating the use of ultrasound-guided lung recruitment. 132 …”
Section: Methodsmentioning
confidence: 99%
“…To define optimal PEEP or guide recruitment by LUS there are different techniques: calculating the LUS score counting B-lines (an artifact), the change in lung sliding (anatomical) or looking for atelectasis at the posterior lateral lung point (anatomical). The first was tested in 24 invasively ventilated C-ARDS patients [ 38 ]. In high recruiters there was a significant decrease in LUS score especially in the lateral and posterior lung regions.…”
Section: Volumes and Aerationmentioning
confidence: 99%